2014
DOI: 10.3402/gha.v7.24912
|View full text |Cite
|
Sign up to set email alerts
|

HIV, multidrug-resistant TB and depressive symptoms: when three conditions collide

Abstract: BackgroundManagement of multidrug-resistant TB (MDR-TB) patients co-infected with human immunodeficiency virus (HIV) is highly challenging. Such patients are subject to long and potentially toxic treatments and may develop a number of different psychiatric illnesses such as anxiety and depressive disorders. A mental health assessment before MDR-TB treatment initiation may assist in early diagnosis and better management of psychiatric illnesses in patients already having two stigmatising and debilitating diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 9 publications
2
43
0
Order By: Relevance
“…Of these seven (16%) patients had depressive symptoms, while 38 did not have baseline depressive symptoms. 32 The results in the present study are on higher side and the percentage of normal patients is 4.62%. Adem A et al had done a study to assess the prevalence of depression in 222 tuberculosis patients and its relationship with regard to socio-demographic factors, disease characteristics, treatment factors and HIV infection.…”
Section: Resultssupporting
confidence: 54%
“…Of these seven (16%) patients had depressive symptoms, while 38 did not have baseline depressive symptoms. 32 The results in the present study are on higher side and the percentage of normal patients is 4.62%. Adem A et al had done a study to assess the prevalence of depression in 222 tuberculosis patients and its relationship with regard to socio-demographic factors, disease characteristics, treatment factors and HIV infection.…”
Section: Resultssupporting
confidence: 54%
“…It was found that the mean of CD4 cell count progression among Another systemic review conducted in 2014 in sub-Saharan African countries found the pooled prevalence of major depressive disorder to be 14.5% (95% CI: 8.9-21.2) [6]. Among studies conducted in India, the prevalence was found to be 16% in Maharashtra, South-West Indian state [7]. Some Indian studies also report higher rates of depression, 49% to 67% [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…WHO staging is a clinical staging of HIV/AIDS patients based on HIV-associated symptoms. It has four stages: asymptomatic, mild symptoms, advance symptoms, and severe symptoms represented by roman numbers I, II, III, and IV, Previous studies have documented a high prevalence of depression among people living with HIV/AIDS (PLHA), varying from 8.1% to 67.3%, quite higher than overall prevalence of depression [2][3][4][5][6][7][8][9][10][11]. Among many comorbidities associated with HIV/AIDS patients, depression ranks higher than most of the others.…”
Section: Study Instrumentsmentioning
confidence: 99%
“…Further, in a rural Andhra Pradesh region of India, it was widely believed that TB is caused by natural and supernatural origins, witchcraft, evil, and imbalance in the quantity of consumption of hot and cold foods and people with TB are considered as those with ill fate (Venkatraju and Prasad, 2010). Severe depressive symptoms were evident in MDR-TB patients, which then improved substantially during the course of treatment (Das et al, 2014). Similarly, psychological impairment in the regions of the brain is associated with family, social and personal activities in TB patients of Delhi region (Bhatia et al, 2000).…”
Section: The Indian Scenariomentioning
confidence: 99%